Agronomic optimal plant density for yield improvement in the major maize regions of China. Issue 3 (9th April 2020) - Luo, Ning; Wang, Xingya; Hou, Jiamin; Wang, Yuanyuan; Wang, Pu; Meng, Qingfeng
Abstract: Identifying the agronomic optimal plant density (AOPD) for maximum grain yield is essential to develop enhanced management strategies for maize ( Zea mays L.) production. In this study, we used a boundary‐line method to examine the yield response of maize to plant density in China, based on the metadata (2783 data points) gathered from 157 recent studies during 2000–2017. We found the AOPD was 8.5 × 10 4 plants ha −1 in Northeast China, 9.3 × 10 4 plants ha −1 on the North China Plain, 10.5 × 10 4 plants ha −1 in Northwest China, and 8.0 × 10 4 plants ha −1 in Southwest China. Compared with current practices, potential grain yield with these AOPDs was improved by 13–20% for these major maize regions of China. Across regions, AOPDs were similar for spring‐planted (9.2 × 10 4 plants ha −1 ) and summer‐planted maize (9.3 × 10 4 plants ha −1 ) systems, although grain yield at the AOPD was 7% greater for the spring‐planted maize system. For different productivity environments, we found that high‐yielding plots obtained a yield of 18.2 Mg ha −1 at an AOPD of 11.6 × 10 4 plants ha −1, whereas in general productivity plots, 39% lower grain yield was achieved with a 19% lower AOPD (9.4 × 10 4 plants ha −1 ). In summary, this study illustrated AOPDs with modern maize hybrids for different productivity environments, cropping systems, and regions. Further study is needed to investigate the possible influence of agronomic factors such as lodging risks by increasing plant density.